(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The core of an organisation is collective behaviour of its employees governed by the organisational culture and shaped by the values,vision and the mission of the organisation. This study is intended to understand – “The Impact of Organisational Culture on Employees’Behaviour in a Research and Development Organisation”. This Empirical research study had primary data collected from 152 middleand lower-level employees of the organisation through a purposive and simple random method using closed ended, properly designedand self-administered survey questionnaire consisting of 50 questions on employees’ demography, organisation culture and behaviours.The data collected was tabulated and descriptive understanding carried out. It was classified and Quantitative Analysis was done usingstatistical software (SPSS) using simple & multiple linear regression techniques, ANOVA and Karl Pearson's Coefficient Correlation toobserve the relation concerning organisational culture and employees’ behaviour. The study reveals that the Research and DevelopmentOrganisation has a mix of technocratic and bureaucratic culture, a progressive association occurs between organisational culture andemployees’ behaviour which further impacts employees’ job performance. This study will help the organisation understand the causes ofemployee & organisation performance problems, assess the effectiveness of motivational practices, address and the correct negativeemployee behaviour pattern and create a healthy work environment for employees. The study is first ever research which discovers theinfluence of organisational culture on employees’ behaviour in Research and Development Establishment, a government of Indiaorganisation. The study will provide valuable insights to the management for cultivating professional perception in the employees, fosterteam-oriented cooperation, boost employee relationship and the establishment’s performance.